2019
DOI: 10.1002/ijc.32742
|View full text |Cite
|
Sign up to set email alerts
|

LEF1 supports metastatic brain colonization by regulating glutathione metabolism and increasing ROS resistance in breast cancer

Abstract: More than half of all brain metastases show infiltrating rather than displacing growth at the macro‐metastasis/organ parenchyma interface (MMPI), a finding associated with shorter survival. The lymphoid enhancer‐binding factor‐1 (LEF1) is an epithelial‐mesenchymal transition (EMT) transcription factor that is commonly overexpressed in brain‐colonizing cancer cells. Here, we overexpressed LEF1 in an in vivo breast cancer brain colonization model. It shortened survival, albeit without engaging EMT at the MMPI. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…LSD1 (lysine-specific demethylase 1) promotes bladder cancer progression by upregulating LEF1 and enhancing EMT [ 9 ]. LEF1 expression may contribute to cancer development [ 26 , 27 , 28 ], but there is a lack of evidence to support malignant phenotype changes, especially motility-associated microstructure changes, such as remodeling of lamellipodia/filopodia based on F-actin/β-tubulin polymerization.…”
Section: Discussionmentioning
confidence: 99%
“…LSD1 (lysine-specific demethylase 1) promotes bladder cancer progression by upregulating LEF1 and enhancing EMT [ 9 ]. LEF1 expression may contribute to cancer development [ 26 , 27 , 28 ], but there is a lack of evidence to support malignant phenotype changes, especially motility-associated microstructure changes, such as remodeling of lamellipodia/filopodia based on F-actin/β-tubulin polymerization.…”
Section: Discussionmentioning
confidence: 99%
“…LEF1 is a transcription factor that promotes the canonical Wnt/β-catenin signaling pathway by cooperating with TCF4 and is pathologically involved in cancer development and progression in multiple cancer types [14]. Previous studies have shown that ectopic LEF1 expression enhances the expression of epithelial-mesenchymal transition (EMT)-related genes, including the epithelial marker E-cadherin and mesenchymal markers N-cadherin, vimentin, ZEB1, and SNAIL, which are involved in cancer metastasis [15,16]. Thus, LEF1 is a promising molecular target for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…These Wnt target genes ( LEF1 and TCF4 ) and YAP ( BIRC5 and ANKRD1 ) target genes have been commonly used in the breast cancer field and are key to the activation of two signaling pathways. [8a,21] In addition, LEF‐1 was also found to support metastatic brain colonization in breast cancer and associated with survival and metastases in chemoresistant TNBC; [ 22 ] YAP target genes BIRC5 promotes proliferation of TNBC cells, and ANKRD1 mediates the growth of breast cancer cells including TNBC cells. [ 23 ] These results suggest a close association between Wnt/YAP signaling, ALDH+ CSCs, and patient survival.…”
Section: Resultsmentioning
confidence: 99%